Sustainable Transportation Infrastructure Development (Case Study: Tanah Bumbu Regency) - Nasruddin, Nasruddin; Radam, Iphan Fitrian; Mahyuni, Mahyuni; Riadi, Selamat; Hadi, Inu Kencana; Dewi, Dyah Hartati; Rahmawati, Rahmawati (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
The development of a region's transportation infrastructure is very important to increase economic growth. Infrastructure is the foundation for Indonesia to be competent with other countries and provides a multiplier impact that can encourage economic growth. This means, that one of the main elements of development policy to support economic activity is the provision of transportation infrastructure. One of the regional governments’ responsibilities is to provide transportation infrastructure as a commodity with a public dimension (public good ). This means that local governments are directly involved in providing transportation infrastructure as a complement to the economic system. The results of this research show that the regional hierarchy of Tanah Bumbu Regency is influenced by population density and the almost even distribution of public facilities, as well as interconnections between regions. For this reason, the Tanah Bumbu Regency government needs to respond to this situation by formulating a strategy for developing sustainable transportation infrastructure.